Independence day - Emmerich, Roland; Devlin, Dean (Twentieth Century Fox Home Entertainment; distributed in the Philippines by Viva Video, 2013)
Massive spaceships appear in Earth's skies and wonder turns to terror as the ships blast destructive beams of fire down on cities all over the planet. The world's only hope lies with a determined band of survivors.